Cancer drug indication approvals in China and the United States: a comparison of approval times and clinical benefit, 2001-2020Research in context - Yuxuan Wei; Yichen Zhang; Ziyue Xu; Guoan Wang; Yue Zhou; Huangqianyu Li; Luwen Shi; Huseyin Naci; Anita K. Wagner; Xiaodong Guan (Elsevier, 2024)
Summary: Background: Perceived delays in cancer drug approvals have been a major concern for policymakers in China. Policies have been implemented to accelerate the launch of new cancer drugs and indications. This study aimed to assess similarities and differences between China and the United States in the approvals, timing, and clinical benefit evidence of cancer drug indications between 2001 and 2020. Methods: This study retrospectively identified all cancer drugs and indications approved in both China and the United States from January 1st, 2001 to December 31, 2020, and described differences in approval times as well as in submission and review times. Information on the availability of overall survival benefit evidence by December 31, 2020, was collected. Univariate and multiple logistic regression analyses were used to assess whether evidence of benefit and other factors affected the propensity and timing of approvals of cancer drug indications in China. Findings: Between 2001 and 2020, 229 indications corresponding to 145 cancer drugs approved in the United States were identified. Of those, 80 indications (34.9%) were also approved in China by the end of 2020. Cancer drug indications were approved in China at a median of 1273.5 days after approval in the United States. The median submission and review time differences for cancer drug indications in China were 1198.0 days and 180.0 days respectively. Submission time differences accounted for most of the approval time differences (p < 0.001). Indications supported by overall survival benefit evidence had shorter median review time differences (145.0 days) than those without such evidence (235.0 days, p = 0.008). Indications with overall survival benefit evidence were 3.94 times more likely to be approved in China compared to those without such evidence (p = 0.001), controlling for approval year, cancer type, and the prevalence of cancer by site. Interpretation: FDA-approved cancer drug indications demonstrating a survival benefit were more likely to receive approvals in China with shorter regulatory review times compared to indications without such evidence. Given that manufacturer submission times were the main driver of cancer drug approval times in China, factors influencing submission timing should be explored. Funding: No funding.